Efeitos de um programa de exercícios físicos na marcha de idosas - Dias, Cláudio Augusto (2016)
The longevity of the population has increased markedly in recent decades, bringing problems arising from aging. One of the problems of the elderly is a decrease in lean body mass, sarcopenia, changing the muscles functions. One of the functions that changes is the walk, motivating this study aims to evaluate the effects of a program of physical exercise in the elderly walk. Material and Methods: descriptive study is, with 12 elderly, who walked by a five-metre course, to capture images of their steps lenght, right (D) and (E). With the images obtained a rating (pre) linear quantitative kinematics of the lengths of the steps lenghts (D) and (E), using the ImajeJ® program for fotogrametrics measurement in centimeters (cm). After this evaluation, over a period of eight weeks, was a Physical Exercise Program (PEF), comprised of nine exercises, to the joints of the hips, knees and ankles, with the use of a latex tube no 201, as resistance to movement. And, subsequently, to the period of the PEF, another assessment was performed (post), where all the PRE assessment procedure was repeated. Statistical analysis between the evaluations was performed using Graphpad software® from Infosoft, with the following tests: 1- t-test for paired samples, comparing the step lengths D and E, before and after the PEF; 2- Wilcoxon test for impaired samples, verifying the variation of the asymmetries between the steps D and E pre and post application of PEF; and; 3-Pearson Correlation Test for verification of correlation between initial step length and variation after application of PEF. Results: three aspects were evaluated: 1-comparison between value of avaliation of PDpré with PDpós and value of avaliation of PEpré with PEpós, found significant differences in values of PD; 2- behavior analysis of the asymmetry between the D and E, PRÉ and PÓS not found significant differences; and; test of correlation between the initial step length and its amendment, finding strong correlations between the greatest lengths of PRÉ, with greater reductions of step lengths in PÓS. Discussion: The results corroborate the results found in other studies, showing a tendency to decrease in lengths of the steps D and E, the bigger the steps D and E initially. The present study presented as weaknesses, the small number of participants, which was also found in other studies with this population, and no checking for PRÉ and PÓS force. Conclusion: the PEF presented was not effective for promoting an increase in the step length D and E, suggesting the studies with a larger number of participants, and perform a PEF taking into account clear Latex tube against the length of the lower limbs.